Global poverty global governance and poor people in the post-2015 era - David Hulme (New York Routledge, Taylor & Francis Group, 2015)
"The first book to tackle the issue of global poverty through the lens of global institutions; this fully updated volume provides an important resource for all students and scholars of international relations, development studies and international political economy"-- Provided by publisher.
Includes bibliographical references and index
Keywords: Poverty--International cooperation